2018
DOI: 10.1111/1753-6405.12790
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of Aboriginal and Torres Strait Islander nutrition in major Australian newspapers, 1996–2015

Abstract: The coverage of Aboriginal and Torres Strait Islander nutrition in newspapers does not reflect the diversity and strengths of Australia's First Peoples. Implications for public health: This study highlights the role of the media in policy advocacy; however, advocates should ensure that they do not perpetuate negative representations of Aboriginal and Torres Strait Islander peoples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 25 publications
(47 reference statements)
1
24
0
2
Order By: Relevance
“…In line with previous studies analysing media representations through content and/or framing analysis, 14,15,19 a combination of content and framing analysis was used to examine the extent and nature of the coverage of nutrition issues, the portrayal of Aboriginal and Torres Strait Islander peoples/communities and inclusion of Aboriginal or Torres Strait Islander voices. The Koori Mail was chosen for analysis due to its status as a community newspaper that specifically covers Aboriginal and Torres Strait Islander issues 34,35 .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In line with previous studies analysing media representations through content and/or framing analysis, 14,15,19 a combination of content and framing analysis was used to examine the extent and nature of the coverage of nutrition issues, the portrayal of Aboriginal and Torres Strait Islander peoples/communities and inclusion of Aboriginal or Torres Strait Islander voices. The Koori Mail was chosen for analysis due to its status as a community newspaper that specifically covers Aboriginal and Torres Strait Islander issues 34,35 .…”
Section: Methodsmentioning
confidence: 99%
“…This study identified six themes linking newspaper reporting and Aboriginal and Torres Strait Islander health policy: highlighting problems, reporting government announcements, promoting programs, advocating solutions, critiquing government and defending policy. The majority of the articles in this study highlighted Aboriginal and Torres Strait Islander nutrition ‘problems’ 15 …”
mentioning
confidence: 94%
See 3 more Smart Citations